Cost‐effectiveness of dementia training for caregivers in caregiver‐patient dyads: A randomized controlled study. Issue 1 (22nd June 2022) - Birkenhäger‐Gillesse, Elizabeth G.; Achterberg, Wilco P.; Janus, Sarah I.M.; Zuidema, Sytse U.; van den Hout, Wilbert B.
Abstract: Introduction: We evaluated the cost‐effectiveness of the "More at Home with Dementia" intervention, a multicomponent training program for co‐residing caregivers of people with dementia (PwDs). Methods: We performed a two‐armed randomized controlled trial with an intervention and a control group. Participants were community‐dwelling caregivers living with a person with dementia (59 randomized to intervention and 50 to control arm). The training program lasted 5 days and took place in a holiday accommodation. Quality‐adjusted life‐years (QALYs) were calculated using the EuroQol‐5 Dimensions 3 Levels (EQ‐5D‐3L) for caregivers and PwDs. Costs for informal and formal social care, as well as health care, were collected at four times over a 6‐month period from baseline. Information on nursing home admission or death was collected for 2 years after baseline. Results: QALYs for caregivers and PwDs added together were 0.12 higher in the intervention group compared with the control group ( P  = .11). After 1 year, there tended to be fewer nursing home admissions in the intervention group, but this difference was lost by 2 years ( P  = .19). The cost of the intervention was estimated at €1000 (USD 1090) per dyad. Compared with the control group, the intervention group used other health care and formal social care significantly less for a year after baseline ( P  = .02 and .001, respectively). The estimated decrease in total costs was €10, 437 ( P  = .07), with an estimated 96% probability that the intervention was cost‐effective vs usual care. Discussion: The multicomponent "More at Home with Dementia" training program is effective and appears to save costs compared with usual care. Savings appear to be achieved by delaying nursing home admissions and by reducing the use of other care resources. Further research is also needed to clarify if this intervention is effective for caregivers who do not live with a PwD, such as adult children, and for the caregivers of patients with other debilitating chronic diseases. At the same time, effort is advised to implement caregiver training in standard care programs.